The Mediterranean Diet and the Increasing Demand of the Olive Oil Sector: Shifts and Environmental Consequences - Neves, Bruno; Pires, Iva Miranda (REGION, 2018)
Mediterranean countries play a crucial role as olive oil producers and consumers compared to other world regions. This work focusses on the development of the world production, trade and consumption where the Mediterranean region stands out from the rest of the world, in particular, the Northern Mediterranean countries. Aspects such as how communication emphasizes the benefits of the Mediterranean diet - which is a distinctive characteristic of the Mediterranean culture and identity - the Slow Food Movement, the International Olive Council campaigns, and the successive Common Agricultural Policies, that have triggered production, trade and consumption around the world, are here discussed. Such increases and stimuli brought and is still bringing changes to the olive oil sector such as a shifting tendency in production modes as well as modernization of the sector, responding to the increasing demand. These shifts and demand are changing landscapes and are being referred as environmentally harmful to the ecosystems as the production of olive oil is shifting to more intensive production systems and monoculture plantations. These issues are here debated and illustrated with case study examples, referring to the Mediterranean countries, particularly, referring to the Iberian Peninsula.